The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/s1479262123000114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of molecular diversity in doubled haploid lines of camelina (Camelina sativa(L.) Crantz), as a new emerging oil crop

Abstract: Camelina (Camelina sativa (L.) Crantz), an oilseed crop, belongs to the Brassicaceae family. Two unique features of camelina in comparison with the main oil crops are an adaptation to different environments and also its unique oil composition. The development of doubled haploid plants is one of the essential methods for crop improvement. The study of genetic diversity is an important step in planning crop breeding programmes. This research was conducted to evaluate the genetic variation of 81 camelina doubled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, it has recently been shown that hybrids between winter and spring forms of C. sativa will have an intermediate phenotype with prolonged vegetation cycle (terms are intermediate between those of the parental genotypes) and often do not require vernalization ( Chaudhary, 2021 ). Crossing genetically distant varieties or obtaining doubled haploid lines from hybrids can be an additional considerable option to increase C. sativa genetic diversity ( Zelt and Schoen, 2016 ; Sadeghikian et al., 2022 ).…”
Section: Higher Genetic Diversity Among Wild Camelina ...mentioning
confidence: 99%
“…In addition, it has recently been shown that hybrids between winter and spring forms of C. sativa will have an intermediate phenotype with prolonged vegetation cycle (terms are intermediate between those of the parental genotypes) and often do not require vernalization ( Chaudhary, 2021 ). Crossing genetically distant varieties or obtaining doubled haploid lines from hybrids can be an additional considerable option to increase C. sativa genetic diversity ( Zelt and Schoen, 2016 ; Sadeghikian et al., 2022 ).…”
Section: Higher Genetic Diversity Among Wild Camelina ...mentioning
confidence: 99%
“…Camelina can be cultivated in semi-arid and temperate regions as a winter-or springsown crop [4]. In recent years, camelina cultivation in Iran has been greatly welcomed and recommended as a suitable oilseed crop for cultivation in Iran's cold rain-fed regions in rotation with cereals [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%